Compliance of the Directions and Programs of Training in Postgraduate Studies: The Transition Period - S. I. Pakhomov; V. A. Gurtov; Yu. N. Berezhnaya (Высшее образование в России)
The new classification of scientific majors for which academic degrees are awarded and the amendments to the Federal Law “On Education in the Russian Federation”, which came into force on September 1, 2021, have significantly changed the list of scientific majors and the status of postgraduate studies. There is a need to establish the correspondence between scientific and pedagogical personnel training directions in postgraduate studies and scientific majors of the Classification 2021, in which academic degrees are awarded. The article presents an analysis of the adapting document “Fields of training in the postgraduate studies of OKSO 2016 – Scientific majors/branches of science of the Classification 2021” and considers measures on the way to reorganize the system of training and certification of academic degree holders.